History Flash: Sejarah “Satu Menit” - Rhoma Dwi Aria Yuliantri (SASDAYA: Gadjah Mada Journal of Humanities, 2018)
This paper elaborates thoughts regarding the use of digital communication technology in the innovation of historical explanation. So far, the explanation of history in the mainstream has set the written explanation (script) as a product of study and thought on historical reconstruction. The script is for sure an important form that has been widely accepted as an output of the past reconstruction. However, technological developments, especially in the field of digital communications, provide historians with new challenges regarding alternative forms of historical representation which confronts the existed conventional models. This paper offers thoughts about the method of historical reconstruction through flash history in the form of short filmmaking, which has the duration in minutes. The objective is to socialize history and bring closer the process of historical reconstruction to the daily life of the community, which currently engages with digital communication technology. The method applied in this study is a historical method. But, the stages and the outputs of this historical method is not a written narrative, but an audio-visual product that can be quickly shared as a learning medium and can be directly addressed by the community. The paper also reviews the limitations of digital technology as media and product in the process of historical reconstruction.